Is the French Emergency Medical Service System duplicable in developing countries?. (13th November 2019) - Rossinot, H; Lapandry, C; Adnet, F; Carli, P; Lecarpentier, E; Baer, M; Veber, F
Abstract: Issue: The management of pre-hospital emergencies is a growing issue in developing countries, particularly because of the increase of both road accidents and cardio-vascular diseases. Description of the problem: Numerous countries have tried or are currently trying to develop emergency response systems like the French SAMU but the outcome of those actions show a lot of difficulties. It is however proved that efficient care of serious pre-hospital medical emergencies significantly improves both patients' mortality and morbidity. Results: AP-HP, Greater Paris University Hospitals, has a strong experience of supporting the development of this model of care in countries with limited resources. Most of last 30 years' experiments have been reviewed to understand what the essential prerequisites to succeed in setting up an emergency response system such as SAMU are. The analysis (5 criteria evaluation: efficiency, sustainability, effectiveness, impact, relevance) of past and present experiments in 28 countries showed that main issues are political (what are the priorities?), financial and societal (what does the population expect?). The question of medical resources is also crucial as the French model introduces medical regulation at all levels. Moreover, in France, such a system is built as a health care pathway with a predetermined orientation towards the appropriate and operational structure, which unfortunately is not the case in a lot of countries. Aside from those realized in China or in some Southern American countries, most of the projects so far don't match all the evaluation criteria, particularly sustainability, as it is based both on stable funding and a strong reactivity of local hospitals. Lessons: Future projects will have to fit with the local context. Strong commitments from partner countries must be made on the long term to have a real impact. Key messages: There is no universal system easily duplicable. Some major prerequisites must be identified and implemented to succeed in the set-up of an efficient and sustainable EMSS.